2021
DOI: 10.1016/j.jaac.2020.11.024
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analytic Review: Psychological Treatment of Subthreshold Depression in Children and Adolescents

Abstract: Objective: Subthreshold depression has been found to be associated with considerable impairment and an increased risk of developing major depression. Although several randomized trials have examined the effects of psychological interventions for subthreshold depression in children and adolescents, no meta-analysis has integrated the results of these trials. Method: We searched 4 bibliographic databases and included randomized trials comparing psychological interventions with control conditions in children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 43 publications
0
51
0
Order By: Relevance
“…org). Trials in children and adolescents were also identified through a recent other meta-analysis of psychotherapies in youth [7,23]. All records were screened by two independent researchers, and all papers that could possibly meet inclusion criteria according to one of the researchers were retrieved as full text.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…org). Trials in children and adolescents were also identified through a recent other meta-analysis of psychotherapies in youth [7,23]. All records were screened by two independent researchers, and all papers that could possibly meet inclusion criteria according to one of the researchers were retrieved as full text.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Thus, new studies provide an important update to this literature and the opportunity to observe how youth and families may be adjusting in the new-onset period of T1D given these recent advances in therapy. In a recent prospective, longitudinal study of 54 adolescents with new-onset T1D, McGill et al [ 52 ] found that 17% had elevated depressive symptoms at 1 month post-diagnosis, which is comparable to rates for youth with established T1D and higher than rates in youth without T1D [ 53 ]. Moreover, this study found that youth reporting elevated depressive symptoms at 1 month post-diagnosis had a higher risk of reporting elevated depressive symptoms at 6 and 12 months post-diagnosis and had a higher HbA1c level at 6 months post-diagnosis than youth who did not report elevated depressive symptoms at 1 month post-diagnosis.…”
Section: Psychosocial Well-being In the New-onset Periodmentioning
confidence: 99%
“…In addition, students' academic performance decline, conflicting with other students due to irritability and then running away from home. [7] Learning Anxiety. Ten children selected in the test lack motivation and efficacy in learning.…”
Section: Severe Anxietymentioning
confidence: 99%